Surface EMG Multichannel Measurements Using Active, Dry Branched Electrodes - Guerrero, Federico Nicolás (2015)
A surface electromiography (sEMG) multichannel aquisition system was implemented using dry electrodes. Branched electrodes were used to obtain spatially selective EMG measurements. Active electrodes coupled with a high dynamic range converter were used to achieve good electromagnetic interference rejection and measurement robustness. Functioning parameters were measured. The device has an equivalent input referred noise less than 1 μV_rms with a voltage gain of 4 , allowing for a ±550 mV electrode offset. The device bandwidth ranges from DC to 500 Hz with a 2000 sps sampling rate. The CMRR is 90 dB further improved by an independent DRL circuit with gain above 30 dB at 50 Hz. Multichannel EMG measurements were successfully conducted and example results are shown.